Unraveling the interplay: early-stage atrial functional mitral regurgitation and left atrial electrical substrate in atrial fibrillation patients - Mohsen, Yazan; Rottländer, Dennis; Großmann, Nora; Lewandowski, Nicole; Horlitz, Marc; Stöckigt, Florian (Frontiers in Cardiovascular Medicine, 2024)
Background: Atrial fibrillation (AF) triggers atrial remodeling, impacting atrial function and ablation efficacy. This remodeling leads to atrial cardiomyopathy and dilatation, linked to mitral regurgitation, forming atrial functional mitral regurgitation (aFMR). Our study explores the relationship between early-stage-aFMR and the atrial electrical architecture, focusing on left atrial bipolar voltage and low-voltage areas (LVAs) in AF patients.We enrolled 282 patients undergoing redo-PVI after AF recurrence post-PVI.Echocardiography was performed prior to ablation, and only patients with no, mild, or mildto-moderate aFMR were included. Ablation used radiofrequency and a 3D mapping system, with atrial voltage documented on each atrial wall. LVAs were calculated using high-density maps, and patients were followed for 15 months. Results: Significant differences in left atrial voltage and LVA extent were observed based on aFMR severity.Patients with aFMR 1+ had significantly lower atrial voltage compared to no-aFMR, but no significant increase in LVAs. Patients with aFMR 2+ showed lower voltage amplitudes in all atrial regions and larger LVAs compared to no-aFMR patients. AF recurrence was significantly higher in the aFMR group (62.9% vs 48.3%, p=0.027) within one year. aFMR was associated with AF recurrence after adjusting for sex, age, and AF types (HR: 1.517, 95% CI: 1.057-2.184, p=0.025). Conclusion: aFMR in AF patients may indicate progressive atrial remodeling and left atrial cardiomyopathy, characterized by reduced atrial voltage and increased LVAs. aFMR is linked to PVI outcomes, suggesting its consideration in AF therapy decision-making.